Kualitas Pelayanan Ditinjau Dari Indeks Kepuasan Masyarakat Pada Poliklinik Yazri Pt Pusri, Palembang - Muhammad Riska Maulana Effendi (EKSISTANSI, 2020)
This research was conductedat the Polyclinic Pusri Yazri PT (Persero) Palembang,  to determine patient satisfaction index in Yazri clinic. By using non-probability sampling method, the research instrument in the form ofa questionnaire distributed to the patients as respondents determined by purposive sampling technique. Determination of the numberof samples based on the calculation of Roscoe. As for the tools used in the analysis with Microsoft Excel, which will be converted back into service satisfaction index, and the results showed that the index patient satisfaction scores with service quality Yazri clinic located at 83 or excellent ratings.